Delitour: A unique dining experience - Capito, Jia Betina Grace L. 4 0 16; 5 (2012)
EXECUTIVE SUMMARY: DeliTour: a unique dining experience, is a restaurant on wheels aiming to promote tourism and the preservation of the Filipino food culture in spite the fast changing generation. The terminal where ordering processes will occur is located in Banco Filipino Condominium Building at Andres Soriano, Jr. Avenue corner Solana Street Intramuros, Manila, across Plaza España, and near the Bureau of Internal Revenue. The restaurant was placed in a very strategic location in Intramuros for it is near the Fort Santiago and the Manila Cathedral, prime tourist spots for both and foreign tourists, and also near the Bureau of Internal Revenue where many people are each day. In addition, the place is found along Andres Soriano, Jr. Avenue, a main road in Intramuros where numerous jeepneys, the Philippines principal mode of transportation, pass along. Therefore, it is assured that the place has enormous number of people, and its accessibility is undeniable. DeliTour is open for business every except Mondays from 9:00am to 6:00pm. Anyone who may have concerns on the business may feel free to reach the restaurant straight through its General Manager, Ms. Jia Betina Grace L. Capito at 0935-880-00-66 ot at (2) 254-55-87. The restaurant caters an all-Filipino menu that is dedicated to be taken in a special dining place - the bus of the restaurant as it makes a 1-hour tour around the walled wonders of Intramuros, a remnant of the Spanish colonial period in the Philippines. The tour will include the following sites in Intramuros: Ayun Tamianeto, Plaza Roam, Intramuros Admin. Will pass by the COMELEC parking, approaching General Luna St. to San Agustin Church and then round trip taking manila way and back to the Terminal. Through this, the business seeks to fulfil its positioning tagline in the minds of the Filipino people-bringing a unique dining experience. For the continuity of the strength and stability of DeliTour, the constituents composing this partnership-type business would allocate Php9,000,000.00 for the start-up capital an would ensure that the profits that will be gained through the business will not be mistreated and will be used effectively. Furthermore, people for different positions will also be hired to handle the different errands that will be involved in the business like a chef and cook for the kitchen, a professional driver for the safety of the trip and the customers while on-board. Later on, DeliTour, is expected to be known as a pioneer in bringing Restobuses in the country, will be able to preserve the Philippine culinary culture, and will become a well-respected company in the Philippine food industry that sustains its consistency both with its corporate and social responsibilities-a fulfilment of its objectives!
Business Plan: (BSBA major in Management)- Pamantasan ng Lungsod ng Maynila, 2018.
Keywords: 2 -- 0; 6; 20; 20; 2